Preparation of ceramic support coating using Tin (II) octoate: effect of polyvinyl alcohol and polyethylene glycol as binders: article - Musa, Muhammad Muzzamil Asyraf; Suhaidi, Amira Nadzirah; Ibrahim, Norliza (2019)
Nowadays, it have been interest to produce immobilized tin (II) octoate catalyst on the surface of the ceramic support for the production of polylactic acid (PLA) from lactic acid (LA) due to easily recycle and separate the catalyst. The objectives of this study is to produce ceramic support coating by using PEG and PVA binders and to characterize the effect of ceramic support coating by using EDX and standard adhesion test. Ceramic powder was obtained from the ceramic waste and used to make the support by mixing with diluted PVA in ratio of 3:1 before compressed and sintered in furnace at 1100⁰C. Then, thin layer of tin (II) octoate was prepared using nitric acid, ethylene glycol (EG) and different types of binders. Dip coating technique was used to coat the thin layer on the ceramic surface before sintered in an oven. Based on the EDX result, the composition of tin present in the thin layer containing PEG binder is 5.50 % compared to 0.46 % composition of tin present in the thin layer containing PVA binder. In additional, result from adhesion test shows thin layer sample containing PEG does not peel off from the ceramic surface while the thin layer containing PVA stick to the tape and peel off from the surface of ceramic at 37.5 %. In conclusion, PEG binder was recommended for the immobilization of high composition of the tin (II) octoate on the ceramic surface.